2020
DOI: 10.1093/ntr/ntaa137
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern and Determinants of Tobacco Use Among Females in India: Evidence From a Nationally Representative Survey

Abstract: Introduction Tobacco use has been steadily increasing among the females in developing countries. It has led to rise in tobacco-related morbidity and mortality among females. Knowing the geographic distribution of the habit is essential to identify high priority areas and direct the healthcare intervention. Hence, this study was done to assess the spatial patterns and determinants of tobacco consumption among females in India. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Much of the previous research on the prevalence of chewing tobacco use has focused on a particular country, 18 , 19 , 20 region, 3 , 4 , 21 source, 3 , 18 , 19 , 20 , 21 time period, 11 , 20 , 21 or age group, 5 , 22 making formation of a comprehensive global picture of where chewing tobacco is used most, among which age groups and sexes, and how these trends have changed over time very difficult. Our study is a step towards understanding this full picture so that policy makers, public health officials, and advocacy organisations have access to a full set of comparable estimates for use in addressing this harmful substance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the previous research on the prevalence of chewing tobacco use has focused on a particular country, 18 , 19 , 20 region, 3 , 4 , 21 source, 3 , 18 , 19 , 20 , 21 time period, 11 , 20 , 21 or age group, 5 , 22 making formation of a comprehensive global picture of where chewing tobacco is used most, among which age groups and sexes, and how these trends have changed over time very difficult. Our study is a step towards understanding this full picture so that policy makers, public health officials, and advocacy organisations have access to a full set of comparable estimates for use in addressing this harmful substance.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we aimed to provide an improved understanding of chewing tobacco use, which is essential for targeted policy, assessment of the effectiveness of these policies, and, ultimately, mitigation of the associated harms. 1 Studies have been done previously that estimated prevalence for a particular country, 18 , 19 , 20 region, 3 , 4 , 21 or source, 3 , 18 , 19 , 20 , 21 or a restricted time period 11 , 20 , 21 or age group, 5 , 22 but to our knowledge no attempt has been made to synthesise multiple data sources to understand these trends globally over time and across age groups. For the first time, as part of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019, we comprehensively estimated the prevalence of chewing tobacco use using all available data sources to estimate age-sex-specific prevalence of chewing tobacco use from 1990 to 2019 in 204 countries and territories.…”
Section: Introductionmentioning
confidence: 99%
“…A study on spatial analysis has shown that clustering of tobacco use among females was also predominant in North-eastern states such as Assam, Manipur, Tripura and Meghalaya. 18 Another recent study also identified some districts of the North-eastern states of India (except Sikkim) as major tobacco hot spots. 19 Hence, the region of North east India can be considered a high priority area in terms of tobacco use.…”
Section: Discussionmentioning
confidence: 98%
“…Researchers have argued that alcohol consumption, illiteracy and tobacco use by any other family member is a predisposing factor of tobacco use (Krishnamoorthy and Ganesh, 2020).…”
Section: Discovery Scientific Societymentioning
confidence: 99%